Trends in Science Education Research on Computational Thinking-STEM Using NVIVO : Literature Review - Mega Elvianasti; Irdalisa Irdalisa; Eka Kartikawati; Bony Irawan (INTERNATIONAL JOURNAL OF HIGH INFORMATION, COMPUTERIZATION, ENGINEERING AND APPLIED SCIENCE (JHICE), 2023)
Science learning in the 21st Century is marked by the improvement and development of students' skills in thinking, acting, and living in the world; 21st-century skills can be developed using various methods, approaches, and learning models. The STEM and Computational Thinking (CT) approach can be a tool for teachers and students in achieving learning goals in the digital era. This paper aims to review the results of research related to CT-STEM in science learning. The research method is carried out by applying the PRISMA protocol. Articles imported from publish or perish come from international journals with a publication range of 2018-2021 then screening is carried out so that ten articles are obtained that are eligible for qualitative testing. After that, coding was carried out using NVIVO 12. The trend of the type of research used by some researchers was a correlative survey, elementary school students were mostly chosen as research subjects, while the most widely used research instruments were computational thinking skills and perception of STEM skills, while for data analysis, The most frequently used are content analysis and descriptive statistics. In addition, there are two articles that combine the CT-STEM approach with learning models, namely: inquiry and PBjL. Regarding the research results, it can be recommended for further research to develop products in the form of learning tools to be able to apply CT-STEM in science learning, especially in Indonesia.